The Assessing Validity of Prima Facie Evidence in Handling the Exception of Jurisdiction in Civil Cases - Dharma Setiawan Negara; Erwin Susilo; Didit Darmawan; Rommy Hardyansah; Lufsiana Lufsiana (JURNAL AKTA, 2026)
The plea of lack of jurisdiction in civil cases is a procedural objection by the defendant challenging the court's authority to adjudicate. Theoretically, it does not involve substantive proof, as it precedes the case's merits. However, judicial practice often includes preliminary evidence, prompting scrutiny of its validity. This study examines the legal foundations of jurisdiction exceptions in Indonesian civil procedure and assesses the admissibility of preliminary evidence. Employing a normative juridical approach with legislative, case, and conceptual analysis, it reviews regulations like the Herzien Inlandsch Reglement (HIR), Rechtreglement voor de Buitengewesten (RBg), and Law No. 48 of 2009 on Judicial Power. Case studies of Interlocutory Decision No. 19/Pdt.Sus-Parpol/2018/PN Cbn and Decision No. 56/Pdt.G/2018/PN Cbn reveal judges accepting preliminary evidence in jurisdiction pleas. Findings indicate that, despite absent explicit rules, this practice aligns with principles of fast, simple, and low-cost justice under Article 2(4) of Law No. 48/2009. To prevent procedural delays, future regulations should restrict evidence to documents, per Positief Wettelijke Bewijstheorie. This research clarifies the legal framework for preliminary evidence in jurisdiction exceptions, enhancing civil justice efficiency in Indonesia.